A arquitetura nas cantigas de Santa Maria - Covre, Bárbara Dantas Batista (2017)
The king Alfonso X believes in the power of the Virgin Mary to overcome the evil. He order scholars and craftsmen to produce the Cantigas de Santa Maria, compendium with more than four hundred reports of miracles and praises to the Virgin, versed in galic